Screening for early-onset invasive group B Streptococcal disease in neonates in an Irish hospital (2001–2014): a retrospective audit. Issue 6 (3rd June 2017) - Nielsen, Maryke; Sheikh, Naveed; Fitzgerald, Eoin; Meehan, Mary; LeBlanc, David; Eogan, Maeve; El-Khuffash, Afif; Drew, Richard J.
Abstract: Group B Streptococcus (GBS) is the most common cause of early-onset neonatal sepsis and meningitis. In babies with no clinical suspicion of infection, who are at risk of early-onset invasive disease based on maternal risk factors, blood cultures are taken to detect bacteraemia. In our institution, lumbar punctures are performed in infants with clinical signs of sepsis but not in infants who are well at the time of screening. Between 2001 and 2014, there were 112, 361 live births weighing >500 g, of whom 13, 959 (12.4%) infants had a blood culture taken on the first or second day of life, and 1971 (14.1%) of these infants had lumbar punctures on these first two days of life. Fifty-three cases of early-onset GBS disease were identified. Only three patients with invasive GBS disease had no clinical suspicion for sepsis at the time of testing. Thus, the number of blood cultures taken to detect one case of GBS bacteraemia in an infant who is well at the time of testing was 3996.